Development, Dissemination, and Assessment of a Food Safety Systems Management Curriculum for Agribusiness Students in Armenia. Issue 4 (10th November 2017) - Pokharel, Siroj; Marcy, Joseph E.; Neilan, Angela M.; Cutter, Catherine N.
Abstract: This study addresses the development, dissemination, and assessment of a Food Safety System Management (FSSM) curriculum offered to college‐aged, agribusiness students in Yerevan, Armenia. Prior to beginning the program, demographic data were collected and a paper‐based pretest was administered to access the food safety knowledge, behavior, and attitude of participants ( n = 29). For assessment of a skill, participants' handwashing techniques were videotaped and scored before the program commenced. Immediately after completion of the entire curriculum, a paper‐based post‐test with identical questions for food safety knowledge, behavior, and attitude was administered and handwashing skills were assessed. ANOVA with repeated measures was used to evaluate significant differences ( α = 0.05) for food safety knowledge using a pretest, post‐test, and a 3‐mo follow‐up. A paired t ‐test was used to evaluate handwashing skills before and after the curriculum was presented. The pretest score (44.93%, ± 2.87) for food safety knowledge ( n = 29) differed significantly ( P <0.0001) when compared with the post‐test score (73.21%, ± 3.28) and the 3‐mo follow‐up ( n = 23) score (67.76%, ± 3.93). Participants' ( n = 9) handwashing skills prior to delivery of the FSSM curriculum differed significantly ( P <0.0001), when compared to handwashing skills after completion of the curriculum. Students' food safety attitudes and behavior assessed using a five‐point Likert scale, also improved significantly as a result of the FSSM program. The 3‐mo follow‐up survey on food safety attitude and behavior was consistent with the post‐test survey results. The information from this project may be of interest to education experts, Extension professionals, food industry personnel, or regulatory agencies, in the development and dissemination of an international food safety program.